Two new species of Araliaceae from the limestone karst of Central Laos - Kongxaisavath, Deuanta; Tagane, Shuichiro; Yamamoto, Takenori; Phonepaseuth, Phongphayboun; Dang, Van-Son; Souladeth, Phetlasy (Phytotaxa, 2026)
Two new species of Araliaceae, Heptapleurum karsticola and Trevesia laotica, are described from limestone karst in central Laos. Heptapleurum karsticola was found in Khammouane Province, and the second species, T. laotica, was found in Bolikhamxai and Khammouane Provinces. Information regarding the distribution, habitat, phenology, vernacular names, preliminary conservation assessment, DNA barcodes, and taxonomic notes compared to other closely related species is provided for each species.